Development of Newsletter Media in Thematic Learning for Elementary School Students - Liliyanti; Azmil Hasan Lubis; Silvia Sandi Wisuda Lubis (MANDAILING GLOBAL EDUKASIA, 2024)
This research is motivated by the limited learning media that can attract students' attention when learning thematic lessons. This research aims to develop bulletin media for thematic learning that is feasible and practical for elementary school students. The research method used is Research and Development using the ADDIE model. The results of the research show that the use of thematic learning bulletin media for class five of State Islamic Primary School 8 Aceh Barat Daya is considered very good for media experts 87%, material experts 75% (good) and language experts 85% (very good). Meanwhile, response data was obtained from 90% of small class teachers (very practical), 92% of large class teachers (very practical). For student response data, 95% of small class students and 95.5% of large class students were obtained and were considered very practical. Based on research results, it shows that the thematic learning bulletin media for class five of State Islamic Primary School 8 Aceh Barat Daya is very practical for use by teachers and students in the teaching and learning process in class